2023
DOI: 10.1111/epi.17651
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory/inhibitory balance in epilepsies and neurodevelopmental disorders: Depolarizing γ‐aminobutyric acid as a common mechanism

Abstract: Epilepsy is one of the most common neurological disorders. Although many factors contribute to epileptogenesis, seizure generation is mostly linked to hyperexcitability due to alterations in excitatory/inhibitory (E/I) balance. The common hypothesis is that reduced inhibition, increased excitation, or both contribute to the etiology of epilepsy. Increasing evidence shows that this view is oversimplistic, and that increased inhibition through depolarizing γ‐aminobutyric acid (GABA) similarly contributes to epil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 133 publications
0
6
0
Order By: Relevance
“…Our MEA results reveal heightened activity in ARX PAE organoids, characterized by increased spikes and bursts recorded from the extracellular space. This elevated activity occurs (abnormally) synchronously in ARX PAE organoids, resembling a pattern indicative of seizures—a condition typically marked by an imbalanced pattern of action potential generation within a neural network 87,88 . According to our findings, the spontaneous hyper spike/burst generation in ARX PAE organoids initiates at 120 DIV and continues through 365 DIV.…”
Section: Discussionmentioning
confidence: 99%
“…Our MEA results reveal heightened activity in ARX PAE organoids, characterized by increased spikes and bursts recorded from the extracellular space. This elevated activity occurs (abnormally) synchronously in ARX PAE organoids, resembling a pattern indicative of seizures—a condition typically marked by an imbalanced pattern of action potential generation within a neural network 87,88 . According to our findings, the spontaneous hyper spike/burst generation in ARX PAE organoids initiates at 120 DIV and continues through 365 DIV.…”
Section: Discussionmentioning
confidence: 99%
“…It also exhibits immune-modulating functions [7] and anti-cancer effects such as the suppression of the proliferation and metastasis of breast [8] and colon cancer cells [9,10]. GABA is closely associated with the regulation of hypothalamic functions, contributing to memory improvement, hormonal regulation [11], and the alleviation of neuroexcitatory disorders such as epilepsy [12]. Previous studies also confirmed the therapeutic effects of GABA in treating asthma [13] and pancreatic dysfunction [14].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, E/I balance is a multifactorial byproduct of neuronal activity, influenced by environmental factors as well as gene expression of channels and receptors 29,30 . Numerous mutations of gene regulating gamma-aminobutyric acid receptors, as well as sodium-potassium channels have been enlisted as etiopathogenic causes of epilepsy 3134 . The recent release of open transcriptomics datasets such as the Allen Human Brain Atlas (AHBA) has offered opportunities to explore how gene expression patterns in the brain reflect macroscale neurofunctional findings 35,36 .…”
Section: Introductionmentioning
confidence: 99%